Adhesive composite joint reinforcement using button shape interlocking features. (October 2020) - Amiri, Mahdi; Farahani, Mohammadreza
Abstract: The composite panels have high strength-to-weight ratio. Adhesive connections are the most common methods of joining in composites. The composite connections are being used in industries such as aerospace, automotive, marine and etc. Low strength is one of the disadvantages of the adhesive connections. Strength improvement is considered in different researches. In this study, using a button shape edge is considered as a new method for strengthening the adhesively bonded composite connections. The effect of geometrical parameters of the button shape edge was investigated numerically and experimentally. These parameters are the radius and height of the button. The influences of the type of the adhesive was also considered in this study. Increasing the radius up to six times the adherent thickness, increased the strength of the joints, significantly. For the optimized geometry (Height = Radius = six times the adherent thickness), the load-bearing capability of the adhesive joint increased up to 300%. Numerical studies showed that the maximum of peel and shear stresses also reduce about 160% and 70%, respectively, for the optimal case. It was also obtained that the height diminution increased the peel and shear stresses in the button shape connections.